Envelhecimento e condicionamento corporal : a perspectiva dos jovens maringaenses que frequentam academias de ginástica - Anacleto, Miriã (2017)
This dissertation describes and analyzes the process of building bodies in gyms, as well as it investigates the perspective of young people who practice physical exercises in these places in relation to the aging and physical conditioning of the body. In a particular way, it discusses the body worship celebrated by modernity and the stigma of old age, and also points out the role of fitness center and urban space in this context. It was written using the quantitative-qualitative research method, the results presented here are the result of the bibliographical review on the subject on body, youth and aging in Anthropology and Sociology; ethnographic work in three gyms located in areas considered middle class in the city of Maringá, located city in the north of Paraná; of the data obtained from the application of questionnaires in one of these gyms and the in-depth interviews conducted with young people who attend this fitness center.